1996
DOI: 10.1073/pnas.93.21.12040
|View full text |Cite
|
Sign up to set email alerts
|

Activation of memory circuits during cue-elicited cocaine craving.

Abstract: Evidence accumulated over more than 45 years has indicated that environmental stimuli can induce craving for drugs of abuse in individuals who have addictive disorders. However, the brain mechanisms that subserve such craving have not been elucidated. Here a positron emission tomographic study shows increased glucose metabolism in cortical and limbic regions implicated in several forms of memory when human volunteers who abuse cocaine are exposed to drug-related stimuli. Correlations of metabolic increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
658
13
10

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 869 publications
(750 citation statements)
references
References 38 publications
69
658
13
10
Order By: Relevance
“…More recently, we and others have shown that repeated administration of drugs of abuse, such as cocaine, affect cellular (Trantham et al, 2002;Nasif et al, 2003) and metabolic functions (Grant et al, 1996;Childress et al, 1999;Volkow and Fowler, 2000) in the PFC. Moreover, it is known that psychomotor stimulants act on limbic and cognitive circuits, and drug-induced neuroadaptations in the corticolimbic circuits are increasingly gaining prominence in hypotheses of drug addiction (Pierce and Kalivas, 1997;Wolf, 1998;Jentsch and Taylor, 1999;Berke and Hyman, 2000).…”
Section: Introductionmentioning
confidence: 79%
“…More recently, we and others have shown that repeated administration of drugs of abuse, such as cocaine, affect cellular (Trantham et al, 2002;Nasif et al, 2003) and metabolic functions (Grant et al, 1996;Childress et al, 1999;Volkow and Fowler, 2000) in the PFC. Moreover, it is known that psychomotor stimulants act on limbic and cognitive circuits, and drug-induced neuroadaptations in the corticolimbic circuits are increasingly gaining prominence in hypotheses of drug addiction (Pierce and Kalivas, 1997;Wolf, 1998;Jentsch and Taylor, 1999;Berke and Hyman, 2000).…”
Section: Introductionmentioning
confidence: 79%
“…Several animal studies have suggested the "extended amygdala" as a neural substrate for the behavioral effects of self-administered cocaine (Robledo and Koob 1993;Caine and Koob 1994;Hurd et al 1997;McGregor and Roberts 1993;Robbins et al 1989;Robledo et al 1996). In humans, recent evidence from brain-imaging studies suggest a role for dopamine-rich brain regions, including the nucleus accumbens and amygdala, in cocaine craving (Grant et al 1996;Breiter et al 1997;Childress et al 1999). Along this line, considering the particular conditions of this work, it is tempting to speculate that, in addition to previously documented inhibition of mesocorticolimbic activity (Rossetti et al 1992;Kuhar and Pilotte 1996), a decrease in proenkephalin gene expression in the Ce may represent a possible mechanism mediating in cocaine withdrawal states.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have consistently revealed increased activation in the OFC, the anterior cingulate, the right insular region, and the amygdala in response to cocaine-related cues (Bonson et al, 2002;Childress et al, 1999;Wang et al 1999;Grant et al, 1996). Other studies have also shown that cocaine abuse is related to a disruption in the striato-thalamo-orbitofrontal circuit (Volkow et al, 1993;Volkow and Fowler, 2000;Goldstein et al, 2001).…”
Section: Introductionmentioning
confidence: 93%